Префиксальные глаголы и их деривационные возможности - Бразaускенe E. (Kalbotyra, 1990)
This article deals with the system of word-formation from productive words and analysis of microsystems of derivatives from different parts of speech in Russian. The analysis of the prefixed verbs as productive words with the complicated derivational structure is of primary importance.